The Existence of Muhammadiyah in Education to Fulfill The Promise of Independence in East Nusa Tenggara - Amirulah Datuk; Arifin Arifin (Jurnal Muhammadiyah Studies, 2024)
This article describes and explains Muhammadiyah's contribution to East Nusa Tenggara. The figure of KH. Ahmad Dahlan, with the Muhammadiyah organization, has answered every need of society, from Islamic renewal to working in the social, preaching, and education sectors. Muhammadiyah has eradicated backwardness, poverty, and ignorance and carried out total resistance against formalism and religious conservatism by breaking down "TBC" (Tahayul, Bid'ah, and Churafat). Because Muhammadiyah truly believes that Islam is a religion that contains progressive values. East Nusa Tenggara is known as an archipelago province because it consists of many islands. The number is more than 500 large and small islands, both named and unnamed. The large islands include Flores Island, Lembata, Sumba, and Alor. The islands that are relatively small and have names include Semau Island, Rinca, Komodo, Permaan, Kojadoi, and many more. The people of East Nusa Tenggara (well known as NTT) are mostly Catholic Christians, more than 55%, Protestant Christians, around 35%, and Muslims, only around 10%. Muhammadiyah locally has an organizational agenda as a response to the conditions of the people in remote areas of the country. While nationally, there is a special agenda related to the needs of the organization. This article uses qualitative methods to analyze the data related to the topics. As a finding, since the beginning of its existence, Muhammadiyah has indeed been intended as a da'wah institution that focuses on strengthening the capacity of the people. Muhammadiyah, in carrying out its mission to educate the nation's generations both before and after independence, can provide an image to the NTT community that Muhammadiyah has actually contributed to fulfilling the promises of independence. This can also be felt by the NTT community, especially in the fields of education, health, and social. This is proven by Muhammadiyah establishing schools, orphanages, and health clinics. Muhammadiyah has contributed a lot to upholding this country on its path. The strength and spirit that have been rooted since 1912 have been able to survive and continue to exist in this beloved country.